THE REQUIREMENT FOR METHODOLOGICALLY WELL-DESIGNED RESEARCH IN DENTISTRY - Arriola Guillén, Luis Ernesto (2025)
Evidence-based dentistry relies on rigorous and structured research conducted by scientists leading well-designed studies.1 These studies must use representative samples taken from the populations they aim to assess. The quality and representativeness of a sample depend on two key factors: its size and the method used for sampling.2 In the materials and methods section of a research article, it is essential to provide a clear and comprehensive explanation of the formula used to calculate the sample size.1,2 Researchers must choose an appropriate sample size formula that aligns with the nature of the outcome variable and the number of groups they intend to compare.2 Unfortunately, a significant number of research articles fall short in this important area, often due to incomplete descriptions or the application of inappropriate formulas that can compromise the external validity of their findings.